MANAJEMEN PENINGKATAN KINERJA GURU PADA SATUAN PENDIDIKAN LANJUTAN MENENGAH PERTAMA KABUPATEN SELUMA - Sakti, Budiman; Ruziandi, Een; Sutardi, Dodo (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
The aims of this study were (1) to analyze the function of planning management in improving teacher performance at SMP Negeri 25 and 34 Seluma Regency, (2) to analyze the management function of organizing in improving teacher performance at SMP Negeri 25 and 34 Seluma Regency, (3) to to analyze the directive management function in improving teacher performance at SMP Negeri 25 and 34 Seluma Regency, (4) To analyze the supervisory management function in improving teacher performance at SMP Negeri 25 and 34 Seluma Regency. This research is a qualitative descriptive study, with the main data sources being school principals, teachers and administrative staff at SMP Negeri 25 and SMP Negeri 34 Seluma. The data analysis used is qualitative analysis assisted by descriptive analysis (explanation). The results of the analysis of the research data obtained show that the management function has not been fully implemented by the principals of SMP Negeri 25 and SMP Negeri 34 Seluma properly. Part of the teacher's performance has not been optimal, as a result of the management function not being carried out optimally.